Introduction to autonomous mobile robots - Siegwart, Roland (Intelligent robotics and autonomous agents., 2004)
This text offers students and other interested readers an overview of the technology of mobility - the mechanisms that allow a mobile robot to move through a real world environment to perform its tasks - including locomotion, sensing, localization and motion planning.